Lex: A Study on Medieval Terminology for Religion. - Ristuccia, Nathan J. (Journal of Religious History, 2019)
Medieval Christian authors frequently employed the Latin word lex ("law") and its vernacular cognates to mean something akin to the modern notion of "religion." Like a religion, a lex was the collection of observances that marked a particular people‐group, such as Christians or Muslims. This article examines the category of lex in its historical context revealing both its similarities and differences from modern "religion." It argues that the category of lex borrowed on Roman ethnography and Patristic exegesis and was inseparable from larger Christian ideas about society, human nature, and political order.